When elephants fight, it's the grass that suffers: organized crime violence and risks for migrants at the U.S.–Mexico border. - Contreras-Velasco, Oscar (Social Forces, 2026)
How does the contestation of territorial control by organized crime shape risks for migrants at the U.S.–Mexico border? Drawing on survey data from nearly 5,000 undocumented migrants (Encuesta sobre Migración en la Frontera Norte [EMIF Norte]), official homicide data from Mexico's National Institute of Statistics and Geography, and U.S. Customs and Border Protection apprehension statistics, this paper combines panel data analysis, negative binomial models, and hierarchical clustering to examine how different forms of criminal territorial control influence migrant risk. I find, first, that contested criminal control, where multiple groups compete for dominance, is associated with significantly higher homicide rates. Second, migrants crossing through these contested territories face higher cumulative exposure to hazards, even after accounting for demographic vulnerabilities and border enforcement. Third, risk is unevenly distributed across the border: migrants crossing through eastern sectors, marked by fragmented and volatile criminal governance, experience higher dangers than those crossing western corridors where criminal authority, while not monolithic, tends to be more consolidated or negotiated. These findings extend sociological theories of non-state governance by showing that criminal organizations can sometimes reduce acute violence when they achieve relative coordination or stability, but that competition and fragmentation undermine this order and amplify migrant vulnerability.